1991
DOI: 10.1152/jappl.1991.70.5.2032
|View full text |Cite
|
Sign up to set email alerts
|

Early muscular and metabolic adaptations to prolonged exercise training in humans

Abstract: A short-term training program involving 2 h of daily exercise at 59% of peak O2 uptake (VO2max) repeated for 10-12 consecutive days was employed to determine the significance of adaptations in energy metabolic potential on alterations in energy metabolism and substrate utilization in working muscle. The initial VO2max determined before training on the eight male subjects was 53.0 +/- 2.0 (SE) ml.kg-1.min-1. Analysis of samples obtained by needle biopsy from the vastus lateralis muscle before exercise (0 min) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
71
2
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 28 publications
15
71
2
2
Order By: Relevance
“…These large functional changes appeared to be directly related to change in the filling dynamics of the left ventricle and may not have been observed in a normal population. Additionally, the magnitude of the changes in ýOµ,max were, in fact, similar to those reported for healthy younger subjects with similar short-term training protocols of 1 or 2 weeks (Green et al 1984(Green et al , 1991Convertino, 1991). Green et al (1991) reported a 250 ml min¢ (±110 ml min¢) increase in ýOµ,max in healthy men aged 19-30 years after 10-12 consecutive days of exercise at 59% of pre-training peak ýOµ,max for 2 h day¢.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These large functional changes appeared to be directly related to change in the filling dynamics of the left ventricle and may not have been observed in a normal population. Additionally, the magnitude of the changes in ýOµ,max were, in fact, similar to those reported for healthy younger subjects with similar short-term training protocols of 1 or 2 weeks (Green et al 1984(Green et al , 1991Convertino, 1991). Green et al (1991) reported a 250 ml min¢ (±110 ml min¢) increase in ýOµ,max in healthy men aged 19-30 years after 10-12 consecutive days of exercise at 59% of pre-training peak ýOµ,max for 2 h day¢.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, the magnitude of the changes in ýOµ,max were, in fact, similar to those reported for healthy younger subjects with similar short-term training protocols of 1 or 2 weeks (Green et al 1984(Green et al , 1991Convertino, 1991). Green et al (1991) reported a 250 ml min¢ (±110 ml min¢) increase in ýOµ,max in healthy men aged 19-30 years after 10-12 consecutive days of exercise at 59% of pre-training peak ýOµ,max for 2 h day¢. Convertino (1991) observed a 340 ml min¢ increase in ýOµ,max in eight young men after 8 consecutive days of exercise -cycling 2 h day¢ at 65% of ýOµ,max.…”
Section: Discussionsupporting
confidence: 79%
“…The muscle metabolic profile was not examined in this study but the intensity of exercise performed by the subjects was similar to that examined in several previous studies which demonstrated glycogen depletion early in exercise (Gollnick et al 1974;Green et al 1991Green et al , 1992Spriet et al 1992). Also, the caffeine dose used (6 mg (kg BM)¢) and the length of the accommodation (60 min) immediately following caffeine ingestion were similar to those previously showing increased time to fatigue (Graham & Spriet, 1991;Spriet et al 1992).…”
Section: ------------------------------------------------------------mentioning
confidence: 79%
“…Whole blood for glucose and lactate was placed in a prechilled tube containing 0.6 M perchloric acid and neutralized in a 1.25 mM KHCO 3, and centrifuged; the supernatant was then analyzed fluorometrically (24). Plasma epinephrine and norepinephrine were measured by HPLC techniques using electrochemical detection as modified by our laboratory (25). For the measurements of the catecholamines, whole blood was collected in a tube containing ethylene glycol-bis (␤-aminoethyl ether) N,N,N 1 ,N 1 -tetra acetic acid and glutathione as antioxidant.…”
Section: Analytical Proceduresmentioning
confidence: 99%